2021
DOI: 10.1200/jco.2021.39.15_suppl.5000
|View full text |Cite
|
Sign up to set email alerts
|

A phase 3 trial with a 2x2 factorial design of abiraterone acetate plus prednisone and/or local radiotherapy in men with de novo metastatic castration-sensitive prostate cancer (mCSPC): First results of PEACE-1.

Abstract: 5000 Background: Historically, androgen deprivation therapy (ADT) was the standard of care (SOC) for men with mCSPC. Since 2015, combining ADT with either docetaxel, novel hormonal therapies, or radiotherapy to the primary tumor (RXT) (for those with low burden metastases) was shown to improve overall survival (OS) and thus has become the new SOC. It is unknown whether combining these new treatments on top of ADT further increments outcomes. Methods: Men with de novo mCSPC were randomized to SOC, SOC + abirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…The recently presented results of the PEACE-1 trial also confirmed the potential benefit of adding abiraterone acetate to docetaxel in men with mHSPC in terms of radiographic PFS (HR 0.50 95% CI 0.40-0.62) [78]; data on OS are awaited before the clinical relevance of this combination can be established. This trial will also provide information about the addition of local radiotherapy to abiraterone acetate in mHSPC.…”
Section: Treatment Combinationsmentioning
confidence: 75%
“…The recently presented results of the PEACE-1 trial also confirmed the potential benefit of adding abiraterone acetate to docetaxel in men with mHSPC in terms of radiographic PFS (HR 0.50 95% CI 0.40-0.62) [78]; data on OS are awaited before the clinical relevance of this combination can be established. This trial will also provide information about the addition of local radiotherapy to abiraterone acetate in mHSPC.…”
Section: Treatment Combinationsmentioning
confidence: 75%
“…This was highlighted in the preliminary results of the PEACE 1 phase 3 trial in which patients were randomized to receive either standard of care (SOC-ADT/bilateral orchidectomy and docetaxel), SOC and abiraterone, SOC and radiation therapy or SOC, abiraterone and radiation therapy. In this study it was proven that the addition of abiraterone to the SOC conferred a benefit of delayed radiological progression and progression to castration resistance [140]. This is an example of improved efficacy of combination therapies.…”
Section: Combination Therapiesmentioning
confidence: 84%
“…It is of note that combination therapies, including chemotherapeutic agents, are likely to play an important role in the near future. Recently, results derived from the PEACE-1 trial demonstrated for example that addition of abiraterone to androgen deprivation therapy (ADT) and docetaxel significantly improved radiographic progression-free survival in de novo metastatic castration sensitive prostate cancer patients ( 17 ). Last, but not least, the current study differed from Weiner et al.…”
Section: Discussionmentioning
confidence: 99%